Dampak Cyberpolitik Terhadap Masyarakat Korea Utara: Studi Kasus Pengendalian Media Sosial di Korea Utara - Robbani, Ahmad Yasin; Novandra, Ardhiata Yasser; Yahya, Afvel Kurnia; Fikri, Haykal; Aji, M. Prakoso (Jurnal Politikom Indonesiana, 2025)
Developments in digital technology have significantly altered the political landscape worldwide, as evidenced by the emergence of cyberpolitics, political activity occurring in the digital realm. However, for countries with authoritarian systems like North Korea, cyberpolitics is used as a means to monitor and repress their citizens. This study aims to analyze the impact of cyberpolitics on North Korean society through a case study of government-implemented social media controls. The methodology used in this study is descriptive qualitative with a desk study approach, examining various literature sources, reports, and academic publications related to information policy and digital surveillance in North Korea. The results of the study indicate that cyberpolitics is implemented in North Korea through three main mechanisms: control of digital infrastructure, censorship and the dissemination of propaganda, and strict monitoring of citizens' online activities. The government restricts its citizens' access to the global internet and replaces it with a national intranet system that is fully controlled by the state, so that information received by the public is only in accordance with government ideology. This situation has resulted in the digital space in North Korea becoming a tool for information monopolization as well as an instrument for shaping political consciousness that benefits the ruling regime. Keywords: Cyberpolitics, Social Media, Information Control, North Korea, Authoritarianisme